Analisis Penggunaan Media Word Wall Untuk Meningkatkan Prestasi Belajar Pada Pembelajaran Bahasa Arab Pada Siswa Kelas IV SDIT Fitrah Insani Kedamaian Bandar Lampung - Sahidatul Umam; Langgeng Sutopo; Angger Putri M (Al Mitsali, 2022)
This research is based on some students who have not been able to read and write and memorize vocabulary properly and correctly. The formulation of the problem in this study is "How is the use of word wall media and learning achievement in learning Arabic in class IV SDIT Fitrah Insani Kedamaian Bandar Lampung students?". While the purpose of this study was "to describe the use of word wall media and learning achievement in learning Arabic in class IV SDIT Fitrah Insani Kedamaian Bandar Lampung students". Therefore the researchers made alternative solutions by using word wall media because it can help students improve learning achievement. The subjects of this study were fourth grade students at SDIT Fitrah Insani Kedamaian Bandar Lampung with a total of 27 students. The form of this research is analysis, the data source used comes from teachers and students. Data collection techniques used are observation, interviews, tests, and documentation. It can be seen that the average score obtained by students in memorizing vocabulary using word wall media is 90.9 with a percentage of 100%. On the test questions the average student score is 90.2 with a percentage of 100%. The conclusion of this study is that the use of word wall media is very effective and can improve learning achievement in learning Arabic in class IV SDIT Fitrah Insani Kedamaian Bandar Lampung